Fundamentals of Phonology: Understanding the Sounds of a Language in Simple Ways - Putri Fadila Ramadhani; Nur Hapsi Harahap; Yani Lubis (Tinta Emas Publisher, 2023)
Phonology is a branch of linguistics that studies the sound system of language. Although it is a complex field, a basic understanding of phonology can help individuals understand and analyze simple language sounds. This abstract aims to present a brief description of the basics of phonology and the importance of understanding phonological principles in linguistic studies. We explore basic concepts such as phonemes, allophones, and phonological rules in forming the sound system of a language. In this abstract, we also underscore the importance of phonology in language teaching and learning. Phonological understanding can help language learners recognize and distinguish similar sounds with different meanings. Through an emphasis on a simplistic approach, this abstract provides a basic understanding that could be used as a foundation for those interested in studying phonology without engaging in complex empirical research. This research was based on a comprehensive literature review of the foundations of phonology. This approach does not involve empirical research or the collection of new primary data but gathers information from relevant secondary sources such as textbooks, academic journals, online articles, and other trusted sources.